14 Genome-wide Association Studies of Disease Resilience Traits from a Natural Polymicrobial Disease Challenge in Pigs. (8th October 2021) - Cheng, Jian; Fernando, Rohan; Cheng, Hao; Kachman, Stephen D; Lim, KyuSang; Harding, John; Dyck, Michael; Fortin, Frederic; Plastow, Graham; Dekkers, Jack C
Abstract: Infectious diseases cause tremendous financial loss in the pork industry, emphasizing the importance of disease resilience, which is the ability of an animal to maintain performance under disease. The objective of this study was to identify quantitative trait loci (QTL) for disease resilience based on both univariate and bivariate genome-wide association studies (GWAS). Data used were late nursery and finisher growth rates and clinical disease phenotypes, including medical treatment and mortality rates, subjective health scores, feed and water intake traits and carcass traits, collected on 50 batches of 60 or 75 crossbred (LRxY) barrows under a polymicrobial natural disease challenge. Multiple QTL were detected for all traits. The major histocompatibility complex (MHC) region (22–25 Mb on chromosome 7) was found to be associated with multiple traits, including late nursery and finisher growth rates, average daily feed intake and intake rate, average daily water dispensed, water intake duration, and number of visits to the drinker. The MHC region explained 13% of genetic variance for late nursery growth rate. Further fine mapping identified four QTL in the MHC region for late nursery growth rate that spanned the class I, II, and III regions. Gene set enrichment analyses found genomic regions associated with resilience phenotypes to be enriched for previously identified disease susceptibility and immune capacity QTL, for genes that were differentially expressed following bacterial or virus infection and immune response, and for gene ontology terms related to immune and inflammatory response. In conclusion, MHC and other QTL identified play an important role in host response to infectious diseases and can be incorporated in selection to improve disease resilience. Funded by Genome Canada, Genome Alberta, USDA-NIFA, and PigGen Canada.